Shadow country a new rendering of the Watson legend - Matthiessen, Peter 1927-2014 (Modern Library, 2008)
Inspired by a near-mythic event of the wild Florida frontier at the turn of the twentieth century, Shadow Country reimagines the legend of the inspired Everglades sugar planter and notorious outlaw E. J. Watson, who drives himself relentlessly toward his own violent end at the hands of neighbors who mostly admired him, in a killing that obsessed his favorite son.--From publisher description.
Keywords: Watson, Edgar J. / 1855-1910 / Fiction; Watson, Edgar J. <1855-1910> - Fiction; Watson, Edgar J. <1855-1910> -- Fiction; Frontier and pioneer life / Fiction; Murderers / Fiction; Frontier and pioneer life - Fiction; Murderers - Fiction; Frontier and pioneer life -- Fiction; Murderers -- Fiction; Everglades (Fla.) / Fiction; Everglades (Fla.) - Fiction; Everglades (Fla.) -- Fiction; Biographical fiction; Historical fiction